Investigation of Patient-Centric 3D-Printed Orodispersible Films Containing Amorphous Aripiprazole - Lee, Ju Hyun; Park, Chulhun; Song, In Ok; Lee, Beom Jin; Kang, Chin Yang; Park, Jun Bom (Pharmaceuticals, 2022)
The objective of this study was to design and evaluate an orodispersible film (ODF) composed of aripiprazole (ARP), prepared using a conventional solvent casting technique, and to fuse a three-dimensional (3D) printing technique with a hot-melt extrusion (HME) filament. Klucel® LF (hydroxypropyl cellulose, HPC) and PE-05JPS® (polyvinyl alcohol, PVA) were used as backbone polymers for 3D printing and solvent casting. HPC-, PVA-, and ARP-loaded filaments were applied for 3D printing using HME. The physicochemical and mechanical properties of the 3D printing filaments and films were optimized based on the composition of the polymers and the processing parameters. The crystalline states of drug and drug-loaded formulations were investigated using differential scanning calorimetry (DSC) and powder X-ray diffraction (XRD). The dissolution and disintegration of the 3D-printed films were faster than those of solvent-cast films. HPC-3D printed film was fully disintegrated within 45 ± 3.5 s. The dissolution rate of HPC films reached 80% within 30 min at pH 1.2 and pH 4.0 USP buffer. There was a difference in the dissolution rate of about 5 to 10% compared to PVA films at the same sampling time. The root mean square of the roughness (Rq) values of each sample were evaluated using atomic force microscopy. The higher the Rq value, the rougher the surface, and the larger the surface area, the more salivary fluid penetrated the film, resulting in faster drug release and disintegration. Specifically, The HPC 3D-printed film showed the highest Rq value (102.868 nm) and average surface roughness (85.007 nm). The puncture strength of 3D-printed films had desirable strength with HPC (0.65 ± 0.27 N/mm2) and PVA (0.93 ± 0.15 N/mm2) to prevent deformation compared to those of marketed film products (over 0.34 N/mm2). In conclusion, combining polymer selection and 3D printing technology could innovatively design ODFs composed of ARP to solve the unmet medical needs of psychiatric patients.
Keywords: 3D printing; aripiprazole; hot-melt extrusion; orodispersible film; patient-centric drug delivery; puncture strength